Mosque Leaders and Management of COVID–19 Pandemic in Ijebu North-East of Ogun State, Nigeria: A Qualitative Survey - Dauda, Kazeem (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2023)
The global response to the December 2019 outbreak of novel coronavirus disease (COVID-19) in Wuhan, China, and its rapid spread to over 200 countries/territories has been intense, with governments, inter-governmental organizations, non-governmental organizations, health and humanitarian agencies, medical experts, and religious institutions all paying close attention. Following the discovery of its index case on February 27, 2020 in Lagos state, Nigeria, various measures were implemented to contain the spread of the deadly virus, including full-cum-partial lockdown, quarantine, and ban on social and religious gatherings, closure of religious centers, among others. The implementation of these COVID-19 Guidelines/Protocols began on March 30, 2020, in the affected states and the Federal Capital Territory (FCT). Religious leaders are thus recognized as key stakeholders in the implementation of these guidelines. Using qualitative and analytical research methods, this paper investigated how mosque leaders in Ijebu North-East responded to the implementation of COVID-19 Guidelines and the challenges encountered in the process. Findings revealed that during the total lockdown, prominent Imams at various central mosques in the local government suspended daily and Jumu‘at congregation prayers, Ramadan Tafsir al-Qur'an, Iftar, Tarawih and Tahajjud, and celebrations of ‘Eid-el-Fitri, ‘Eid-el-Adha and Mawlud-en-Nabiyy. During the de-escalation of the lockdown, the NCDC’s COVID-19 Guidelines on Re-Opening Places of Worship were strictly followed. Inadequate resources, misconceptions, and a sense of disbelief among some Muslims in the existence of COVID-19 are among the identified challenges. The study concludes by suggesting how mosque leaders can proactively assist governments in eradicating coronavirus and related diseases.